2007
DOI: 10.1071/rd07021
|View full text |Cite
|
Sign up to set email alerts
|

Follicle stimulating hormone and fibroblast growth factor-2 interact and promote goat primordial follicle development in vitro

Abstract: The aims of the present study were to investigate the effects of the interaction between follicle stimulating hormone (FSH) and fibroblast growth factor-2 (FGF-2) on survival, follicular growth initiation and further growth of caprine preantral follicles. Pieces of caprine ovarian cortex were cultured for 1 or 7 days in minimum essential medium (MEM) supplemented with FSH, FGF-2 or FSH + FGF-2. Small fragments from non-cultured ovarian tissue and from those cultured for 1 or 7 days were processed for classical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 38 publications
4
45
0
Order By: Relevance
“…In contrast, the other treatments (FSH-7d and FSH + FGF-2) were effective in maintaining follicle ultrastructural integrity up to day 7. Our light histological results confirm earlier studies in which FSH maintained preantral follicle viability after short (Matos et al, 2007a andMatos et al, 2007c) or long-term culture (Cortvrindt et al, 1997, Wright et al, 1999and Gutierrez et al, 2000. It is suggested that the absence of FSH in the medium could compromise the diffusion of several essential chemical and physical factors through the basement membrane (Hsueh et al, 1994).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In contrast, the other treatments (FSH-7d and FSH + FGF-2) were effective in maintaining follicle ultrastructural integrity up to day 7. Our light histological results confirm earlier studies in which FSH maintained preantral follicle viability after short (Matos et al, 2007a andMatos et al, 2007c) or long-term culture (Cortvrindt et al, 1997, Wright et al, 1999and Gutierrez et al, 2000. It is suggested that the absence of FSH in the medium could compromise the diffusion of several essential chemical and physical factors through the basement membrane (Hsueh et al, 1994).…”
Section: Discussionsupporting
confidence: 89%
“…Thus, some follicles could die after activation due to an improper environment for continuing their normal development (Rüsse, 1983). Recently, we have demonstrated that FSH could improve caprine follicular activation (Matos et al, 2007a andMatos et al, 2007c). In addition, Joyce et al (1999) reported that FSH stimulates Kit ligand mRNA expression in the granulosa cells of preantral follicles, which is essential for the initiation of primordial follicle growth (Parrot and Skinner, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations